PENDAMPINGAN PENENTUAN HARGA POKOK PRODUKSI (HPP) DAN HARGA JUAL PADA UMKM DI DESA BUSUNG - Charly Marlinda; Ranti Utami; Rachmad Chartady; Putri Dwi Novrina; Novica Indriaty (Bajang Institute, 2025)
This community service activity was conducted to assist MSME (Micro, Small, and Medium Enterprises) actors in Busung Village, Seri Kuala Lobam Subdistrict, Bintan Regency, in understanding the concept of Cost of Goods Manufactured (COGM) and determining the appropriate selling price for their products. Busung Village is an archipelago region where most of the population are fishermen and face economic limitations due to weather conditions. This program aims to enable MSMEs to accurately calculate COGM, allowing them to set competitive and profitable selling prices. The activity was carried out door- to-door, providing individual guidance. The methods used included interviews, socialization, training, and understanding evaluations. The results of the assistance indicated a significant increase in MSME actors' understanding of COGM and product pricing. Thus, this program positively contributes to improving business management skills for the residents of Busung Village